Female sexual dysfunction among Malaysian women in a primary care setting: Does the frequency of sexual activity matter? - Hatta Sidi,; Sharifah Ezat Wan Puteh,; Marhani Midin,; Norni Abdullah, (Penerbit UKM, 2007)
The aim of the study was to compare sexual functioning among Malaysian women in a primary care setting between those with a low and high frequency sexual intercourse.Across-sectional study on 230 married Malaysian women in a primary-care setting was conducted at the Bandar Tun Razak Clinic, Cheras. A validated Malay version of Female Sexual Function Index questionnaire (MVFSFI) was used to assess the sexual functioning profiles among women with low and high sexual activity. The percentage of women who had sexual intercourse 3-4 times a week, 1-2 times a week and < 1-2 times a month were 13.4%, 44.3 % and 42.4 % respectively. Women with a low frequency of sexual intercourse (Low SI) tended to suffer from more sexual dysfunction, (χ²=28.98, p < 0.001) compared to those with a high frequency of sexual intercourse (High SI) group. Women who were less sexually active (having low frequency intercourse, ie. ≤ 1 – 2 times per week) were found to be less sexually aroused (χ²= 25.9, p< 0.001), less orgasmic (χ²=19.8, p< 0.001), less lubricated during sexual activity (χ²=11.1, p< 0.001), complain of sexual pain (χ²=4.3, p = 0.033) and feels less satisfied sexually (χ²=12.6, p< 0.001).The problem of female sexual dysfunction (FSD) in the Malaysian primary care population with low sexual activity needs to be addressed